Rola Eucharystii w walce z szatanem u Ojców Kościoła - Borkowska, Małgorzata (Vox Patrum, 1987)
Although the Desert Fathers did not speak often about Eucharist, there are passages in their conferences showing that they had a great cult of the holy Mysteries and set a great value upon acquiring orthodox notions of it.